2008
DOI: 10.1007/s12026-008-8028-y
|View full text |Cite
|
Sign up to set email alerts
|

Complement and cutaneous autoimmune blistering diseases

Abstract: Cutaneous autoimmune blistering diseases are associated with tissue injury and fluid accumulation within the skin. The initial trigger for the organ-specific damage is autoantibodies targeting skin autoantigens, which are involved in cell-cell or cell-matrix adhesion in the skin. Pemphigus autoantibodies bind to desmosomal antigens and cause intraepidermal blisters, while pemphigoid autoantibodies interact with hemidesmosomal or hemidesmosome-associated antigens and lead to dermal-epidermal junction separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…The pathogenicity of anti-BP180 antibodies was first confirmed in vivo by passively transferring them into neonatal mice [28]. Studies using this experimental model revealed that subepidermal blistering triggered by anti-BP180 IgG depends on complement (C3 and C5) activation, by both the CP, and to a lesser extent, the AP, leading to generation of C5a and its binding to C5aR, followed by mast cell degranulation and neutrophilic infiltration (reviewed in [29]). Further experiments have identified FcγRIII as the only crucial receptor for the pathogenicity of anti-BP180 IgG, although the role of FcγRI or FcγRIV could not be excluded or investigated at that time [30].…”
Section: Murine Models Of Autoimmune Subepidermal Blistering Diseasesmentioning
confidence: 99%
“…The pathogenicity of anti-BP180 antibodies was first confirmed in vivo by passively transferring them into neonatal mice [28]. Studies using this experimental model revealed that subepidermal blistering triggered by anti-BP180 IgG depends on complement (C3 and C5) activation, by both the CP, and to a lesser extent, the AP, leading to generation of C5a and its binding to C5aR, followed by mast cell degranulation and neutrophilic infiltration (reviewed in [29]). Further experiments have identified FcγRIII as the only crucial receptor for the pathogenicity of anti-BP180 IgG, although the role of FcγRI or FcγRIV could not be excluded or investigated at that time [30].…”
Section: Murine Models Of Autoimmune Subepidermal Blistering Diseasesmentioning
confidence: 99%
“…It appears that there is no correlation between antibody titers and the extension or activity of the disease. 3,28,43 Epidermolisis bullosa acquisita/ Bullous systemic lupus erithematosus IIF: It shows circulating anti-BMZ IgG antibodies in 25-50% of the patients. There is no correlation between antibody titers and the extension or activity of the disease.…”
Section: -1842mentioning
confidence: 99%
“…Specific markers of active T-cells and B-cells have been commonly characterised in humans with autoimmune blistering diseases (Sitaru & Zillikens, 2005). Furthermore, it is important to note that an association between epidermal-specific auto-antibodies and complement proteins has been described previously in human pemphigus (Lessey et al, 2008;Qian et al, 2011); a cross-reaction among IgE, IgM, and IgG4 anti-DSG-1 response has been reported in human PF patients (Qian et al, 2011). In contrast, IgM autoreactivity was not detected when canine PF serum was used against either DSG-1 or DSC-1 (Bizikova et al, 2014), and canine PF showed dominant IgG auto-antibody reactivity (Pérez et al, 2002: Olivry et al, 2009).…”
Section: Discussionmentioning
confidence: 95%